2022
DOI: 10.1001/jama.2022.16310
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Depression and Suicide Risk in Children and Adolescents

Abstract: ImportanceDepression, suicidal ideation, and self-harm behaviors in youth are associated with functional impairment and suicide.ObjectiveTo review the evidence on screening for depression or suicide risk in children and adolescents to inform the US Preventive Services Task Force (USPSTF).Data SourcesPubMed, Cochrane Library, PsycINFO, CINAHL, and trial registries through July 19, 2021; references, experts, and surveillance through June 1, 2022.Study SelectionEnglish-language, randomized clinical trials (RCTs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
68
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(68 citation statements)
references
References 78 publications
0
68
0
Order By: Relevance
“…Adolescent depression is common, and almost 70% of adolescents who have a depressive disorder will have a recurrence within five years, with a four-fold risk of experiencing depression in adulthood [ 4 , 14 , 15 ]. Suicide is the second most common cause of death in this age group, with the rate of depression and suicide worsening in industrialized countries [ 16 , 17 , 18 ]. Any substantial improvements in the treatment of adolescent depression would clearly be welcomed.…”
Section: The Problemmentioning
confidence: 99%
“…Adolescent depression is common, and almost 70% of adolescents who have a depressive disorder will have a recurrence within five years, with a four-fold risk of experiencing depression in adulthood [ 4 , 14 , 15 ]. Suicide is the second most common cause of death in this age group, with the rate of depression and suicide worsening in industrialized countries [ 16 , 17 , 18 ]. Any substantial improvements in the treatment of adolescent depression would clearly be welcomed.…”
Section: The Problemmentioning
confidence: 99%
“…For depression, there were studies that demonstrated benefit, but these studies were rated low strength of evidence and likely contributed to the B recommendation (high certainty that the net benefit is moderate, or there is moderate certainty that the net benefit is moderate to substantial) for depression screening in the current recommendations, similar to the 2016 USPSTF recommendations . For suicide, the current USPSTF review identified 16 randomized clinical trials that were of good or fair quality. However, pooled results for suicide outcomes and measures of psychosocial functioning found no significant differences in these outcomes except on 1 measure (reported benefits on suicidal ideation) …”
mentioning
confidence: 96%
“…In this issue of JAMA , the USPSTF presents an updated Recommendation Statement on screening for depression and suicide risk in children and adolescents, along with an updated Evidence Report and Systematic Review by Viswanathan et al that serves as the basis for current recommendations. In 2014, the USPSTF published recommendations on screening for suicide risk in adolescents and adults and in 2016, on screening for depression in children and adolescents .…”
mentioning
confidence: 99%
See 2 more Smart Citations